Dreaming in patients with epilepsy: a cross‐sectional cohort study - Maïlis Charpentier‐Hélary; Aurélien de la Chapelle; Morgane Linard; Nathalie André‐Obadia; Sébastien Boulogne; Hélène Catenoix; Julien Jung; Sylvain Rheims; Katharina Schiller; Birgit Frauscher; Perrine Ruby; Laure Peter‐Derex (2025)
Epilepsy impacts cognition during wakefulness. As epileptic activity is present and even augmented during sleep, epilepsy could also influence sleep-related cognitive processes. However, whether epilepsy modulates sleep-related experiences like dreaming remains poorly known. Here, we prospectively investigated the characteristics and determinants of dreaming in patients with epilepsy. Consecutive adult patients with epilepsy and no major cognitive deficit were recruited in an epilepsy outpatient clinic. They completed a questionnaire about their dreams, sleep and epilepsy over the past year. Medical data on epilepsy characteristics were gathered from the medical file. A generalised linear model was used to explore the determinants of dream recall frequency (DRF). We included 300 patients, with a mean (standard deviation [SD]) age of 40.4 (13.4) years and 51.3% female; 28.6% had more than one seizure/month, and 34.7% already had seizures during sleep. Patients recalled dreams on an average of 1.6 (1.5) days/week and 11% had one or more nightmare/week. Younger age, higher number of nocturnal awakenings, and lower seizures frequency predicted a higher DRF. In patients with focal epilepsy (65.3%), the localisation of the epileptic focus in the parieto-occipital area was negatively associated with DRF. Regarding dream content, 34.0% of patients reported having already dreamt about epilepsy. Dreams of seizures were associated with sleep-related seizures (p = 0.034) and dreams of epilepsy were associated with nightmare frequency (p = 0.004). Our results show that patients with epilepsy share several determinants of DRF (age, awakenings, role of the parieto-occipital area) with healthy subjects. In addition, epilepsy-related factors (seizure frequency, focus localisation) also impact DRF. Investigating dreams in patients with epilepsy can provide information on their epilepsy and their sleep.